Risks associated with cryopreserved semen in a human sperm bank during and after the COVID-19 pandemic. Issue 3 (March 2021) - Huang, Chuan; Zhou, Shuai-Feng; Gao, Li-Dong; Li, Shi-Kang; Cheng, Yu; Zhou, Wen-Jun; Huang, Zeng-Hui; Ji, Xi-Ren; Fan, Li-Qing; Zhang, Fan; Chen, Zi-Wei; Zhan, Zhi-Fei; et al.
Abstract: Research question: What are the risks associated with cryopreserved semen collected during and after the coronavirus disease 2019 (COVID-19) pandemic wave in Wuhan, China? Design: Retrospective cohort study involving young adult men who were qualified sperm donors at the Hunan Province Human Sperm Bank (China) during the pandemic wave (1 January 2020 to 30 January 2020) and after the wave and return to work (7 April 2020 to 30 May 30 2020). One hundred paired semen and blood specimens from 100 donors were included. One-step single-tube nested quantitative real-time polymerase chain reaction (OSN-qRT-PCR) was used to detect SARS-CoV-2. Moreover, to control the unacceptable risk of false-negative results, a second round of screening was performed with pooled RNA from negative semen samples using crystal digital PCR (cd-PCR). Results: For individual blood and semen samples, the target genes, namely the nucleocapsid protein (N) and open reading frame (ORF-1ab) genes, tested negative in all of the 100 paired samples. Further, as per cd-PCR results, there were >20, 000 droplets per well in the RNA for each combined sample and no positive droplets were present for either of the aforementioned target genes. A total of 100 paired semen and blood samples from these two groups tested negative for SARS-CoV-2. Conclusions: Cryopreserved semen at the Hunan Province Human Sperm Bank during and after the COVID-19 pandemic wave was free of SARS-CoV-2 and was judged safe for external use in the future.